The Effects of the Pandemic on Mexican Federalism and on the Redefinition of the Role of Local Governments - Carrera Hernández, Ady Patricia (Revista del CLAD Reforma y Democracia, 2021)
The pandemic affecting the global community since the early 2020, has had deep repercussions. Most of the world’s governments have been unable to manage the problem successfully, while subnational governments have tried to meet the immediate demands of their communities facing the crisis. The responses have been as diverse as the results, but it is possible to distinguish important coincidences in the Latin American federations. Among them is the ineffectiveness of intergovernmental coordination mechanisms to generate a well-organized response. In this situation, subnational governments have taken actions that have trespassed on the powers of the national government or even ignored its dispositions. In the case of Mexico, is compounded by the economic stagnation that existed prior to the pandemic, as well as an important political current, coming from various state governments, which had been demanding a revision of the federal arrangement in the face of the intensification of the recentralization process adopted by the current federal administration. This paper analyses the way in which all these factors have affected local management and the implications this has for the country’s development.
Keywords: Federalism; Local Government; Intergovernmental Relations; Coordination; Crisis Management; Mexico